Are shocks to disaggregated renewable energy consumption permanent or temporary for the USA? Wavelet based unit root test with smooth structural shifts. (15th September 2020) - Aydin, Mucahit; Pata, Ugur Korkut
Abstract: Non-stationary renewable energy consumption can be permanently affected by supply, demand and policy shocks, and in this case renewable energy promoting policies can be implemented effectively. It is therefore important to determine which type of renewable energy is stationary. To this end, we introduce a new wavelet-based unit root test which takes into account the smooth structural changes and frequency components in the series. With this method we investigate the stationary of the renewable energy consumption for the US over the period 1973m01-2019m09. To compare the results, we also use conventional ADF and wavelet-based ADF unit root tests that do not take into account structural breaks. The findings of the wavelet-based Fourier ADF unit root test indicate that biofuels energy consumption is stationary, while geothermal, waste, and wind energy consumption are non-stationary. Furthermore, the findings of the wavelet-based ADF unit root test indicate that while hydropower energy consumption is stationary at levels, solar, wood, total biomass, and total renewable energy consumption contain a unit root. Overall, we conclude that renewable energy policies implemented in the US have permanent effects on seven types of renewable energy consumption, whereas these policies have temporary effects on hydropower and biofuels energy consumption. Highlights: The paper proposed a new wavelet-based unit root test with Smooth Structural Shifts. The permanency of shocks on disaggregated renewable energy consumption was investigated. Nine types of renewable energy consumption data was used. The shocks have permanent effects on renewable energy consumption except hydropower and wind.